Effects of USB port access on advanced cookstove adoption. (2018) - Wilson, Daniel L.; Monga, Meenakshi; Saksena, Abhinav; Kumar, Advait; Gadgil, Ashok
Abstract: Three billion people cook using traditional fires, and exposure to smoke from cooking remains a persistent and significant environmental health risk factor: household air pollution is estimated to cause 3–4 million premature deaths per year. "Improved cookstoves" could reduce the health risks associated with cooking, but the performance of most improved cookstoves is insufficient to result in meaningful health benefits, and global adoption of low-emission cookstoves remains low. However, a new class of advanced cookstoves equipped with thermoelectric generators could improve both emissions performance and adoption leading to better health outcomes. These cookstoves use electrical power provided by a thermoelectric generator to power combustion-improving fans while powering outboard USB charging ports. In communities lacking electricity access, USB levels of power could provide much-needed off-grid charging for mobile phones, small lights, and other loads. However, there is a risk that instead of being used primarily as a cooking tool, these cookstoves could be used solely as fire-powered USB chargers. Without displacing traditional cookstoves, "charging-only" adoption would result in a net increase in emissions exposure. In this study, we used custom Advanced Stove Use Monitor (ASUM) sensors to measure adoption of TEG-equipped cookstoves in 72 rural homes without electricity access in Odisha, India. To measure the impacts of the USB charging port, we randomized whether recipients received a cookstove with USB ports enabled or disabled. We found that access to USB charging ports significant increased adoption of cookstoves in "cooking" use modes; USB-enabled cookstoves were used for cooking 3.5X more than identical cookstoves with disabled USB ports. This substantial increase in cooking came with a relatively small marginal use of the cookstove in a "charging-only" mode; just 11% of total cookstove use was in this mode. As with past work, data showed that surveys of user behavior do not correlate well with sensor-measured behavior. The trial cookstove was much smaller and more cumbersome than traditional cookstoves, but still, we found that users were willing to prepare fuel and found the cookstove useful for light cooking tasks. Access to USB charging served as a catalyst for adoption of advanced cookstoves as cooking tools and did not increase undesirable "charging only" adoption modes. This work suggests that these kinds of USB-enabled cookstoves could be an important tool to improve biomass combustion, increase adoption, and realize meaningful health benefits.